The Effectiveness of Using Augmented Reality Media in Mathematics Learning in Primary School: A Systematic Literature Review (SLR) - Mufarrahatus Syarifah; Adi Atmoko; Ratna Ekawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyse the effectiveness of Augmented Reality (AR) technology in mathematics learning in primary schools through a Systematic Literature Review (SLR) conducted in accordance with the PRISMA guidelines. The review process consists of four main stages, namely identification, screening, eligibility, and inclusion. The data sources were obtained from articles indexed in Scopus published between 2016 and 2025, which used quantitative or mixed-methods approaches and involved primary school students as subjects. Fifteen articles met the inclusion criteria and were analyzed further. Findings confirmed that AR technology is efficacious in improving students' spatial skills, critical thinking, and drive to learn. In addition, AR improves long-term memory retention and makes geometric concepts, such as rotation and spatial orientation, more tangible. From an affective standpoint, using AR makes learning fun and can help children feel less anxious about mathematics. Overall, the effectiveness of AR is multidimensional, covering the cognitive, affective, and psychomotor domains. The limitation of this study lies in the restricted scope of data sources and research types, which may limit the generalizability and contextual depth of the findings. As a recommendation, further research is needed to explore the use of AR in greater depth to strengthen mathematical thinking and reasoning skills.